2012
DOI: 10.2337/db11-1034
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study of Gestational Diabetes Mellitus in Korean Women

Abstract: Knowledge regarding the genetic risk loci for gestational diabetes mellitus (GDM) is still limited. In this study, we performed a two-stage genome-wide association analysis in Korean women. In the stage 1 genome scan, 468 women with GDM and 1,242 nondiabetic control women were compared using 2.19 million genotyped or imputed markers. We selected 11 loci for further genotyping in stage 2 samples of 931 case and 783 control subjects. The joint effect of stage 1 plus stage 2 studies was analyzed by meta-analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
222
4
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(247 citation statements)
references
References 52 publications
17
222
4
4
Order By: Relevance
“…We are aware of only one published GWAS of GDM to date. This was conducted among Korean women and demonstrated a potentially shared genetic basis between GDM and type 2 diabetes [9]. Emerging data also indicate a possible environmental aetiology for GDM.…”
mentioning
confidence: 99%
“…We are aware of only one published GWAS of GDM to date. This was conducted among Korean women and demonstrated a potentially shared genetic basis between GDM and type 2 diabetes [9]. Emerging data also indicate a possible environmental aetiology for GDM.…”
mentioning
confidence: 99%
“…Our previous investigation has shown that women with Japanese GDM have beta cell dysfunction irrespective of presence or absence of overweight [25]. Regarding the genetic background, several studies revealed risk variants related to insulin secretion in Korean and Chinese population [36][37][38][39][40][41]. Of the three genetic variants found in this study, two are related to the regulation of insulin secretion (i.e.…”
Section: Discussionmentioning
confidence: 89%
“…The findings that maternal age at delivery, pre-pregnancy BMI and the rate of overweight were comparable between the GDM and NGT groups are important. Therefore, our study cohort is suitable to investigate GDM risk genes, as were suggested in previous reports [8,40].…”
Section: Discussionmentioning
confidence: 97%
“…For example, if it is found that genetic variants associated with high blood pressure and glucose intolerance/type 2 diabetes in general populations of men and nonpregnant women are also associated with HDP and GDM, this would lend some support to the hypothesis of a common etiology and pregnancy unmasking a preexisting (genetic) risk. There is some evidence that several type 2 diabetes mellitus variants from genome-wide association studies show robust associations with GDM (Karlsson et al 2007;Lauenborg et al 2009;Cho et al 2009;Kwak et al 2012). …”
Section: Data and Methods Development Prioritiesmentioning
confidence: 99%